Severe hypokalemic paralysis and rhabdomyolysis occurring after binge eating in a young bodybuilder: Case report. Issue 40 (October 2017) - Lee, Tae Won; Bae, Eunjin; Hwang, Kyungo; Jang, Ha Nee; Park, Hee Jung; Jeon, Dae-Hong; Cho, Hyun Seop; Chang, Se-Ho; Park, Dong Jun
Abstract: Rationale: Severe hypokalemia can be a potentially life-threatening disorder and is associated with variable degrees of skeletal muscle weakness. Patient concerns: We report a case of severe hypokalemic paralysis and rhabdomyolysis in a 28-year-old bodybuilder. He was admitted to the emergency room due to progressive paralysis in both lower extremities, which had begun 12 hours earlier. He was a bodybuilder trainer and had participated in a regional competition 5 days earlier. He went on a binge, consuming large amounts of carbohydrates over 4 days, resulting in a gain of 10 kg in weight. Diagnoses: He had no family history of paralysis and this was his first attack. He strongly denied drug abuse, such as anabolic steroids, thyroid and growth hormone, and diuretics. Neurological examinations revealed symmetrical flaccid paralysis in his lower extremities, but the patient was alert and his sensory system was intact. His initial serum potassium and phosphate level was 1.8 mmol/L and 1.4 mg/dL, respectively. The calculated transtubular potassium gradient (TTKG) was 2.02. His thyroid function was normal. Interventions and Outcomes: Serum potassium levels increased to 3.8 mmol/L with intravenous infusion of about 50 mmol of potassium chloride over 20 hours. Outcomes: His muscular symptoms improved progressively and he was discharged from the hospital 7 days after admission on foot. He was followed in our outpatient clinic, without recurrence. Lessons: Physicians should keep in mind that large intakes of food during short periods can provoke hypokalemic paralysis and rhabdomyolysis, especially in bodybuilders.